Lexicon annotation in sentiment analysis for dialectal Arabic: systematic review of current trends and future directions - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Lexicon annotation in sentiment analysis for dialectal Arabic: systematic review of current trends and future directions by Alamoodi, Abdullah Hussein